2021
DOI: 10.1088/1755-1315/883/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Level of escherichia coli contamination of broiler chicken meat in Ambon City Market

Abstract: Chicken meat is a source of animal protein that is very popular with all people, especially in Indonesia. The meat also contains nutrients that are good for the body. However, broiler meat also has a weakness because it is a food that is easily damaged; most of the damage is caused by poor handling, thus providing opportunities for growth microbes. Broiler meat is easily contaminated by various microorganisms that are in the environment. This study aimed to determine the level of microbial contamination in bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other results mostly show broiler chicken meat contaminated with E. coli , which was probably because of poor sanitation standards of water used in the cutting and processing of chicken meat ( 28 ). All the positive pig-origin strains were isolated from carcass swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Other results mostly show broiler chicken meat contaminated with E. coli , which was probably because of poor sanitation standards of water used in the cutting and processing of chicken meat ( 28 ). All the positive pig-origin strains were isolated from carcass swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these contents are higher than the study reported [13] which stated tha the ash content of local chicken meat is 1.0%. The ash content will increase as the age of chicken increased [14]. ) and KUB Murung Panggang (1.97-3.97%) were higher than the study reported [15] stated that carbohydrate content of meat is 0.5-1.0%.…”
Section: Ashmentioning
confidence: 70%